(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction: Examination of morphological and morphometric features of the retina, retinal nerve fiber layer, choroidea in patients with posttraumatic endophthalmitis after pars plana lens vitrectomy using spectral-domain optical coherence tomography is very important for understanding its development and search for new complex methods of treatment. Purpose. To study morphological and morphometric features of the retina, retinal nerve fiber layer, choroidea in patients with posttraumatic endophthalmitis after pars plana lens vitrectomy using spectral-domain optical coherence tomography (OCT) by Spectralis (Heidelberg Engineering). Material and methods. We observed 11 patients (11 eyes) with posttraumatic endophthalmitis. Pars plana lens vitrectomy was performed in all cases in terms of 3—28 days after injury. 1 month after surgery the retina and retinal nerve fiber layer were examined in 5patients, choroidea — in 4patients using OCT. Results. Our data show increase of the macular retinal thickness especially in the central region. Thickness of the retinal nerve fiber layer also increased in the trauma-tized eyes. Choroidal thickness decreased in the macular andparapapillar regions. Conclusion. It was first of using spectral-domain optical coherence tomography by Spectralis (Heidelberg Engineering) in patients with posttraumatic endophthalmitis after pars plana lens vitrectomy. In our cases we observed increase of the retinal thickness in the macular region, increase of thickness of the retinal nerve fiber layer, decrease of choroidea in the macular and parapapillar regions.